Debris Flows Occurrence in the Semiarid Central Andes under Climate Change Scenario - Moreiras, Stella Maris (2021)
This review paper compiles research related to debris flows and hyperconcentrated flows in the central Andes (30°–33° S), updating the knowledge of these phenomena in this semiarid region. Continuous records of these phenomena are lacking through the Andean region; intense precipitations, sudden snowmelt, increased temperatures on high relief mountain areas, and permafrost degradation are related to violent flow discharges. Documented catastrophic consequences related to these geoclimatic events highlight the need to improve their understanding in order to prepare the Andean communities for this latent danger. An amplified impact is expected not only due to environmental changes potentially linked to climate change but also due to rising exposure linked to urban expansion toward more susceptible or unstable areas. This review highlights as well the need for the implementation of preventive measures to reduce the negative impacts and vulnerability of the Andean communities in the global warming context.